2015
DOI: 10.12928/pharmaciana.v5i2.2145
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Sistem Imun Oleh Kombinasi Ekstrak Etanol Daun Awar – Awar (Ficus Septica Burm. F) Dan Ekstrak Etanol Daun Kelor (Moringa Oleifera) Sebagai Ko-Kemoterapi Kanker Pada Tikus Putih Betina Galur Sprague Dawley Yang Diinduksi Doksorubisin

Abstract: ABSTRAKPenggunaan obat doksorubisin untuk terapi kanker menyebabkan sistem imun tubuh menurun. Daun awar-awar dan daun kelor merupakan tanaman herbal yang memiliki manfaat sebagai agen imunostimulan atau meningkatkan sistem kekebalan tubuh. Adapun tujuan penelitian ini untuk mengetahui efek kombinasi ekstrak etanol daun awar-awar dan ekstrak etanol daun kelor sebagai kokemoterapi kanker pada tikus putih betina galur Sprague Dawley yang terinduksi doksorubisin. Delapan belas ekor tikus Sprague Dawley dibagi men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…showed that a single dose of 500 mg/kgBB dose of moringa leaf ethanol extract had more effective activity as an immunostimulator against CD3+ and CD8+ when compared to a single dose of ethanol extract of 750 mg/kgBB, suggesting that ethanol extract groups and moringa leaves had a more effective ability to boost the immune system. 7 And research conducted by Fathir et al (2014:114-120) showed that giving moringa leaf extract can increase the number of CD4+ T cells and CD8+ T cells in all mice infected with salmonella thypi and the administration of high doses of moringa leaf extract causes immunosuppression and can also serve as immunostimulated and immunosuppression in CD4+ T cells and CD8+ mice, this is due to an increase in the number of CD8+ T cells affected by the presence of active substances in moringa leaf extracts. Saponins and flavonoids that can stimulate increased IL-2 in CD4+ T cells and increased IL-2 also allow for an increase in the number of CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that a single dose of 500 mg/kgBB dose of moringa leaf ethanol extract had more effective activity as an immunostimulator against CD3+ and CD8+ when compared to a single dose of ethanol extract of 750 mg/kgBB, suggesting that ethanol extract groups and moringa leaves had a more effective ability to boost the immune system. 7 And research conducted by Fathir et al (2014:114-120) showed that giving moringa leaf extract can increase the number of CD4+ T cells and CD8+ T cells in all mice infected with salmonella thypi and the administration of high doses of moringa leaf extract causes immunosuppression and can also serve as immunostimulated and immunosuppression in CD4+ T cells and CD8+ mice, this is due to an increase in the number of CD8+ T cells affected by the presence of active substances in moringa leaf extracts. Saponins and flavonoids that can stimulate increased IL-2 in CD4+ T cells and increased IL-2 also allow for an increase in the number of CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sari et al , it was stated that mice given ethanol extract and moringa leaves of 500 mg/kgBB within 7 consecutive days had effective immunostimulatory activity against CD3+ and CD8+. 7 Therefore, the proportion of moringa leaves given according to the weight of mice is 500 mg/1000 gr = 1:2, 80 mg/160 gr = 1: 2. 80 mg = 0.08 gr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mangrove leaves play an important role in improving the survival rate due to their ability to improve shrimp health. Avicennia marina leaf extract contains flavonoid compounds that can act as antimicrobial, antibacterial, antiviral, and immunostimulants (Sari et al, 2015). The mechanism of flavonoids as antibacterial can be divided into three: the inhibition of nucleic acid synthesis, the inhibition of cell membrane function, and the inhibition of energy metabolism (Rijayanti, 2014).Alkaloids are antibacterial, but they work by destruct the peptidoglycan component in bacterial cells, resulting in the formation of imperfect cell wall layers, thereby causing the bacterial cell to die (Mufti et al, 2022).…”
Section: Survival Rate (Sr)mentioning
confidence: 99%
“…Avicennia marina can promote growth, boost the immune system and stimulate the feeding response in aquaculture. Flavonoids can act as antimicrobial, antibacterial, antiviral and immunostimulants (Sari et al, 2015). Adding immunostimulants into the feed has been an effective method to improve non-specific defense systems (Irkin and Yigit, 2015).…”
Section: Introductionmentioning
confidence: 99%